Historical definition and theoretical background of usury loan provisions - Zuzana Chlumská (Financial Internet Quarterly, 2021)
The thesis deals with usury and illegal lenders both on the domestic scene and abroad. The usury itself is defined by its characteristics, by adjudication and by historical connotations. The historical definition begins in Mesopotamia and ancient Rome, basically since the emergence of money. The aim of the paper is a comprehensive overview of usury, which from the legal perspective is not precisely defined as a term and the thesis tries to find such a definition with the help of case law and interpretation. The characteristics of usury that are described in the thesis are distress, the presence of a weaker party, mental weakness, and a gross disparity of performance. The thesis also describes the history of loan sharks and usury in the United States, where violence plays a considerable part in the issue. The paper also deals with the social background of usury and illegal lenders in the United Kingdom and outlines possible solutions to eradicate these phenomena in financially disadvantaged communities. In the end the thesis attempts to find unifying characteristics of usury across history and said countries.
Keywords: G53; K15; P37; 330; usury; adjudication; lending; interest rates; history; criminal offense; financial literacy